Framing chronic absenteeism and emotionally-based school absenteeism as public health problems - Christopher A. Kearney (Frontiers in Child and Adolescent Psychiatry)
Chronic school absenteeism (CSA) and emotionally-based school absenteeism or avoidance (EBSA) are highly prevalent conditions linked to multiple short- and long-term problems across academic, social-emotional, physical and mental health, family, and occupational and economic domains of functioning. In addition, CSA and EBSA occur disproportionately across vulnerable student groups and have been the focus of extensive preventative and intervention efforts. As such, CSA and EBSA may meet criteria as formal public health problems. This perspective article illustrates various ways of framing CSA and EBSA in this fashion utilizing contemporary public health models. Categories of public health models are emphasized in this regard and include ecological, systems and policy, epidemiologic and statistical, environmental and occupational, and behavioral and social science approaches. Each approach closely parallels research and other work regarding school absenteeism. The article is designed as a step toward advocacy for recognizing CSA and EBSA as formal public health problems contingent upon consensus among key constituencies in this area.